A framework for use in modelling the modal choice decision making process in North West England’s Atlantic Gateway - Bury, Alan (Logistics and sustainable transport, 2017)
The task of producing a generic model of the modal choice decision making process is a challenging one. Modal choice is strongly influenced by the infrastructure limitations and geographical constraints of the area in which the decision is being made. With this in mind, addressing modal choice on an individual basis for each region may be the optimal solution. This is the approach adopted in this paper. The creation of a modal choice model is a multistage process of which this paper addresses the first stage, the production a framework of the decision making process. Firstly, a number of criteria that are commonly used in modal choice models are identified. Then a number of gaps in the criteria utilized in previous papers are established. Subsequently, the method used to produce a framework of the decision making process within North West England’s Atlantic Gateway is outlined. Through consultation with transport industry experts in North West England, an initial list of sixty eight papers was reduced to thirty six that were considered to be of specific relevance to modern day freight transportation within their region. The criteria used in each of these papers were then, along with further industry input, used to create the foundation on which a modal choice framework specific to the Atlantic Gateway could be built. A greater understanding of what influences modal choice within this region will allow informed decisions to be made by policy makers on how to more efficiently utilize the available modes of freight transport. Having established this, future work can then go on to build upon these findings. This paper recommends that future work is performed to establish the weights of each criteria and sub-criteria within the framework. This should then be followed by establishing industry’s perceptions of the best and worst alternatives for moving freight within the Atlantic Gateway.
Keywords: Atlantic Gateway; freight transport; modal choice; modalna izbira; North West England; Northern powerhouse; severozahodna Anglija; tovorni promet